2000
DOI: 10.1063/1.373189
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic phase transitions in (Fe1−xTx)3Ga4 alloys

Abstract: The magnetic ordering in the series of transition metal alloys (Fe1−xTx)3Ga4 with T=Ni and Ti having values of x in the range 0.05⩽x⩽0.20 has been investigated at high fields and low temperatures. Magnetization measurements revealed that in contrast to other T substitutions, Ni and Ti induce completely different types of effects on the magnetic properties. In the case of Ni substitution a ferrimagnetic-like type of magnetic order is induced at low compositions and low temperatures and Ti produces a ferromagnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It has been shown that doping can effectively tune the IDSW to FM transition temperature as well as the low temperature FM to ISDW transition. 16,[28][29][30][31] Similarly, previous work has shown that external pressure is effective at tun- ing the low temperature FM-ISDW transition temperature, but the effect on the high temperature ISDW-FM transition temperature has not been reported. 20,32 From these works, it appears that intermediate IDSW is sensitive to effects caused by doping through electron count changes and/or structural changes which in turn effect the electronic structure in this regime; although this has not be rigorously studied.…”
Section: Introductionmentioning
confidence: 96%
“…It has been shown that doping can effectively tune the IDSW to FM transition temperature as well as the low temperature FM to ISDW transition. 16,[28][29][30][31] Similarly, previous work has shown that external pressure is effective at tun- ing the low temperature FM-ISDW transition temperature, but the effect on the high temperature ISDW-FM transition temperature has not been reported. 20,32 From these works, it appears that intermediate IDSW is sensitive to effects caused by doping through electron count changes and/or structural changes which in turn effect the electronic structure in this regime; although this has not be rigorously studied.…”
Section: Introductionmentioning
confidence: 96%